Acute Liver Failure in Patients with Classic Heat Stroke - Jeremy J. Hernández-Ríos; Fátima María Martínez-González; Luz A. Gutiérrez-Bañales; J. Andrés Beltrán-López; Hiram J. Jaramillo-Ramírez (University Library System, University of Pittsburgh, 2020)
Background: Classic heat stroke is defined by a core temperature greater than 40° C, severe dehydration and neurological alterations. Patients with liver disease due to heat stroke have been described, mostly by exercise. Hepatic failure is defined as the presence of a coagulopathy accompanied by any degree of hepatic encephalopathy. The primary objective of the study lies in the fact that patients who developed acute liver failure during their hospital stay had a higher risk of mortality. Methods: A retrospective, analytical study of patients admitted to the General Hospital of Mexicali who suffered from classic heat stroke from March 2006 through August 2010, and a second period from June 2018 to August 2019. Results: Fifty patients were recruited, the group included 48 (96%) male, with a total of 10 fatalities, representing 20%. INR greater than 1.5, AST and ALT levels were not related to an increased mortality rate. Conclusion: Neither transaminase levels, nor liver failure, were related to a higher mortality rate in this cohort of patients with classic heat stroke.